Determining University Students’ Smoking Habits and Awareness Levels About Thirdhand Smoke - Salimoğlu, Serap; Çağatay, Hüseyin Tolga; Akdur, Recep (Addicta: The Turkish Journal on Addictions, 2023)
This study aims to determine students' smoking status and their awareness level about thirdhand smoke. A web-based questionnaire was applied to 367 students who agreed to participate in the descriptive study. Thirdhand Smoke Awareness Scale was used. The scale was adapted into Turkish by Önal et al in 2021. Confirmatory factor analysis determined the compatibility of the data with the scale. Of the participants, 23.2% are male and 76.8% are female. Acceptable fit indices were reached in the analysis. Cronbach's alpha value was found to be .91. The rate of smokers in the last 30 days is 46%. It was determined that 47.4% of smokers smoke every day. The rate of those who do not know what thirdhand smoke is was determined as 84.5%. No significant difference was found between the awareness levels of the participants according to gender, family structure, place of residence, education level of parents, and economic status of the family (p > .05). The fact that the concept of thirdhand smoke has not yet been heard by many does not change the fact that it exists and has certain adverse effects. This research is vital in showing the need for awareness studies on the subject.
Keywords: Cigarette; smoking; student; thirdhand smoke; tobacco